(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides information about the field of cognitive linguistics, which is one of the important areas of modern linguistics. Language units that realize the concept of "life/death" in English and Uzbek languages of different systems are compared at different levels and their field nature is comparatively studied. Linguistic units in the area of the concept of life/death are considered through examples from different literature. At the same time, its language units are thoroughly explored and summarized through examples at language levels. The analysis reveals isomorphic and allamorphic aspects of the concept of purpose in English and Uzbek languages..